2018
DOI: 10.1007/s11605-018-3731-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Endoscopic Ultrasound-Guided Biliary Drainage (EUS-BD) for Malignant Biliary Obstruction Associated with Ascites: Results of a Pilot Study

Abstract: EUS-BD is technically feasible in patients with ascites. Our results suggest that EUS-BD may be a clinically effective and safe alternative after failed ERCP in patients with ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, a recent pilot study found that EUS-BD was technically feasible and clinically effective and safe even in patients with ascites. 34 In this study, the presence of a small amount of perihepatic ascites was observed in seven patients (17.5%) on CT obtained prior to EUS-BD. However, similar to the previous report, EUS-BD could be safely performed without severe AEs, including bile peritonitis.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, a recent pilot study found that EUS-BD was technically feasible and clinically effective and safe even in patients with ascites. 34 In this study, the presence of a small amount of perihepatic ascites was observed in seven patients (17.5%) on CT obtained prior to EUS-BD. However, similar to the previous report, EUS-BD could be safely performed without severe AEs, including bile peritonitis.…”
Section: Discussionmentioning
confidence: 50%
“…The volume of ascites or duodenal stents was also not associated with adverse events. Alvarez et al 29 also reported that EUS-BD was technically and clinically effective and safe in patients with ascites. In this study, two patients with ascites on the puncture line were withdrawn before puncture because the fistula was not formed and the risk of bile leakage or peritonitis may be increased if ascites are present on the puncture line.…”
Section: Discussionmentioning
confidence: 95%
“…Also, a study has shown that it is better in patients who have ascites. 225 Q54. When is surgical biliary drainage indicated?…”
Section: Remarksmentioning
confidence: 99%